2016
DOI: 10.4238/gmr.15038019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods to preserve Rheum palmatum (Polygonaceae) for efficient DNA extraction and PCR amplification

Abstract: ABSTRACT. In this study, we compared the quality of DNA extracted using the modified CTAB method, from Rheum palmatum leaves preserved using fourteen different methods, including ones used commonly in other species: under ultra-cold (-80°C) temperatures, after drying with an absorbent paper, desiccating using a silica gel, drying at 60°C, in 70% ethanol, absolute ethanol, 70% ethanol supplemented with 50 mM EDTA, SDS-DNA extracting solution, nuclear separation buffer, improved NaCl-CTAB solution, TE-buffer, I-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…precipitation ), which apparently did not occur in the samples, id fragments. The same was not observed for R. , for which conservation methods influenced DNA quality CTAB were not amplified, ded high quality fragments (Huang et al, 2016b). In , storage with silica gel made it impossible to amplify the 20 ºC favored the preservation of the samples (Feres et al, study, it should be noted that oxidation of phenolic compounds present in the leaf samples of mate stored in CTAB, at room temperature for 90 days, did not impede DNA amplification.…”
Section: Rheum Palmatummentioning
confidence: 86%
See 3 more Smart Citations
“…precipitation ), which apparently did not occur in the samples, id fragments. The same was not observed for R. , for which conservation methods influenced DNA quality CTAB were not amplified, ded high quality fragments (Huang et al, 2016b). In , storage with silica gel made it impossible to amplify the 20 ºC favored the preservation of the samples (Feres et al, study, it should be noted that oxidation of phenolic compounds present in the leaf samples of mate stored in CTAB, at room temperature for 90 days, did not impede DNA amplification.…”
Section: Rheum Palmatummentioning
confidence: 86%
“…Methods for storing and extracting DNA from DNA extraction in CTAB buffer was not successful from leaves of Huang et al, 2016 From the analysis of the amplification products of the plastid fragment we observed that with all of the storage methods, or with fresh leaves, we obtained DNA without the presence of residues that impede the acti Inappropriate storage methods may result in DNA degradation, as well as co of PCR inhibitors (Huang et al, 2016b), which apparently did not occur in the samples, since there was amplification of the plastid fragments. The same was not observed for K. lathrophyton, for which conservation methods influenced DNA quality and PCR reactions.…”
Section: Netics and Molecular Research 18 (3): Gmr18390mentioning
confidence: 99%
See 2 more Smart Citations
“…Preserving DNA through deactivation of nucleases, removal of cations or lowering temperature becomes crucial to inhibit enzymes that degrade DNA. Most studies have utilized freezing conditions (Carroll et al, 2012;Wu et al, 2012) or the use of preservatives such as ethanol (Murphy et al, 2002;Bressan et al, 2014;Huang et al, 2016), RNAlater (Nechvatal et al, 2008;Sorensen et al, 2016), and glycerol:PBS (McKain et al, 2013;Fliegerova et al, 2014) to preserve bacterial DNA before extraction. However, few studies have examined the combination of chemical buffers and temperature reduction to preserve DNA and optimize bacterial analysis.…”
Section: Introductionmentioning
confidence: 99%